Measuring Meiotic Crossovers via Multi-Locus Genotyping of Single Pollen Grains in Barley - Dreissig, Steven; Fuchs, Jörg; Cápal, Petr; Kettles, Nicola; Byrne, Ed; Houben, Andreas (PLoS One, 2015)
The detection of meiotic crossovers in crop plants currently relies on scoring DNA markers in a segregating population or cytological visualization. We investigated the feasibility of using flow-sorted haploid nuclei, Phi29 DNA polymerase-based whole-genome-amplification (WGA) and multi-locus KASP-genotyping to measure meiotic crossovers in individual barley pollen grains. To demonstrate the proof of concept, we used 24 gene-based physically mapped single nucleotide polymorphisms to genotype the WGA products of 50 single pollen nuclei. The number of crossovers per chromosome, recombination frequencies along chromosome 3H and segregation distortion were analysed and compared to a doubled haploid (DH) population of the same genotype. The number of crossovers and chromosome wide recombination frequencies show that this approach is able to produce results that resemble those obtained from other methods in a biologically meaningful way. Only the segregation distortion was found to be lower in the pollen population than in DH plants.
Keywords: genom rostlinný; DNA rostlinná; Genome, Plant; Recombination, Genetic; lokus kvantitativního znaku; Meiosis; Hordeum; Multilocus Sequence Typing; pyl; ječmen (rod); Pollen; haploidie; Quantitative Trait Loci; chromozomy rostlin; Haploidy; crossing over (genetika); multilokusová sekvenční typizace; Crossing Over, Genetic; rekombinace genetická; DNA, Plant; meióza; Chromosomes, Plant